The synthesis of the cyclometallated palladium complexes and their applications in olefin oligomerization and in phenylacetylene oligomerization/polymerization - Mungwe, Nothando Wandile (2014)
Magister Scientiae - MSc === This thesis reports the synthesis of the imine ligands from Schiff base condensation reaction of aldehyde derivatives and equimolar quantities of aniline derivatives. The imine ligands spectrometry.